Legal Protection for Victims of Trafficking in Persons From a Human Rights Perspective: Perlindungan Hukum bagi Korban Tindak Pidana Perdagangan Orang Ditinjau dari Perspektif Hak Asasi Manusia - Oktavionita, Falen; Riyadh, Ahmad (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the legal protection for victims of trafficking in persons in terms of human rights perspective. This research is based on the fact that there are still cases of trafficking in persons and the protection of victims is still not effective. Victims are entitled to protection according to human rights guidelines. The author conducted this research using a normative research method using a statutory approach related to the object under study and also using a conceptual approach. The data collection technique used is secondary data consisting of primary legal materials, namely legislation and secondary legal materials in the form of books, scientific papers and data obtained. This study explains that a person who is a victim of trafficking in persons is entitled to protection in accordance with the provisions of the legislation as well as the provision of compensation rights to victims of trafficking in persons according to the human rights inherent in him. And this study also discusses the role of the government and the community in an effort to provide protection for victims of trafficking in persons to uphold human rights.